PERILAKU DISOLUSI KETOPROFEN DAN INDOMETASIN FARNESIL TERSALUT GEL KITOSAN-GOM GUAR - Sugita, Purwantiningsih; Srijanto, Bambang; arifin, budi; amelia, fithri; mubarok, mahdi (Badan Pengkajian dan Penerapan Teknologi, 2010)
Chitosan, a modification of shrimp-shell waste, has been utilized as microcapsule. However, it’s fragile gel property needs to be strengthened by adding glutaraldehyde (glu) and natural hydrocolloid guar gum (gg). This research’s purposes were to study dissolution behaviour of ketoprofen and infar through optimum chitosan-guar gum microcapsule. Into 228.6 mL of 1.75% (w/v) chitosan solution in 1% (v/v) acetic acid,38.1 mL of gg solution was added with concentration variation of 0.35, 0.55, and 0.75% (w/v) for ketoprofen microcapsules and 0.05, 0.19, and 0.33% (w/v) for infar microcapsules, and stirred with magnetic stirrer until homogenous. Afterwards, 7.62mL of glu was added slowly under stirring, with concentrations varied: 3, 3.5, and 4% (v/v) for ketoprofen microcapsules, and 4, 4.5, and 5% (v/v) for infar microcapsules. All mixtures were shaked for 20 minutes for homogenization. All mixtures wereshaked for 20 minutes for homogenization. Into each microcapsule mixture for ketoprofen, a solution of 2 g of ketoprofen in 250 mL of 96% ethanol was added, whereas solution of 100 mg of in 250 mL of 96% ethanol was added into each microcapsule mixture for infar. Every mixture was then added with 5 mL of 2% Tween-80 and stirred with magnetic stirrer for an hour at room temperature. Everymixture was then added with 5 mL of 2% Tween-80 and stirred with magnetic stirrer for an hour at room temperature. Conversion of suspension into fine powders/granules (microcapsules) was done by using spray dryer. The data of [gg], [glu], and medicine’s content from each microcapsule were treated with Minitab 14 software to obtain optimum [gg] and [glu] for microencapsulation. The dissolution behaviour of optimum ketoprofen and infar microcapsules were investigated. The result of optimization by using Minitab Release 14 software showed that among the microcapsule compositions of [gg] and [glu] were 0.35% (w/v) and 3.75% (v/v), respectively, optimum to coat ketoprofen, whereas [gg] and [glu] of 0.05% (w/v) and4.00% (v/v), respectively, optimum to coat infar, at constant chitosan concentration (1.75% [w/v]). In vitro dissolution profile showed that chitosan-guar gum gel microcapsule was more resistant in intestinal pH condition (rather basic) compared with that in gastric pH (very acidic).